Improvement of Turbulent Burning Velocity Measurements by Schlieren Technique, for High Pressure Isooctane-Air Premixed Flames. Issue 3 (3rd March 2020) - Brequigny, Pierre; Endouard, Charles; Foucher, Fabrice; Mounaïm-Rousselle, Christine
ABSTRACT: As in most industrial cases, the expansion of premixed flames in spark-ignition (SI) engines is strongly affected by turbulence flow fields. However, as the flame radius and curvature are non-negligible during combustion development, the global stretch effect can drastically change the turbulent flame propagation speed. In this paper, spherical turbulent premixed flames were studied inside a constant-volume vessel for a wide range of air-isooctane mixtures, initial turbulent intensities and pressures by using simultaneously Mie scattering tomography and 2-View Schlieren imaging. The comparison between different radii enabled non-convected flames with a global spherical shape to be selected and the validity of a correction factor, first introduced by Bradley et al., was assessed. A set of turbulent flame speeds was obtained and the evolution as a function of the global stretch rate was analyzed. Various turbulent flame speed definitions were also evaluated on two different datasets.